Mobile Telecommunication Network (MTN) and Corporate Social Responsibility in Benue State: An Assessment of Socio-Economic Impact - TSUWA, John Tor; ANYAGH, Ngufan (Socialscientia: Journal of Social Sciences and Humanities, 2023)
This study assessed Mobile Telecommunication Network (MTN) and Corporate Social Responsibility in Benue State, 2005-2020 with particular references to an assessment of socio-economic impact. The specific objectives of the study were to (a) examine the economic responsibility of Mobile Telecommunication Network (MTN) in Benue State and (b) assess the social-cultural responsibility of Mobile Telecommunication Network (MTN) in Benue State. A survey research design was adopted, and a total of 400 respondents were sampled out of the population of 2,901,500. Data was analysed using descriptive statistical tools of percentages, frequency tables and column charts to establish the contributions of MTN to the Corporate Social Responsibility (CSR) in Benue State. The study found that in Benue MTN has contributed to revenue generation (through indirect employment), the sales of MTN products (recharge cards, SIM Cards) creates employment, it generates revenue for government through payment of taxes, MTN undertakes advertisement activities (radio and television jingles) thereby contributing to revenue generation too. Furthermore, MTN in Benue State is involved in academic and educational programmes, facilitates specialised education and training (enhancing literacy level), providing scholarship to indigent and brilliant students, execution of educational projects (classrooms, laboratories and libraries), supports women empowerment as well as encouraging sports development. It was therefore, recommended that MTN should set up functional mechanism that will facilitate a good level of partnership with the host community so that members will maximally benefit from it by generating income/revenue, employment among others. Efforts should be made on the part of the government to domesticate the provisions of the International Corporate Responsibility Instrument. For instance, MTN should approach the indigenous stakeholders so as to identify vital aspects of culture so to incorporate it in their Corporate Responsibility Instrument.